THE ROLE OF STUDENT LEADERSHIP EXERCISE IN DEVELOPING WORK DICIPLINE TOWARD STUDENTS ORGANIZATION. ( Study Kasus Association Of Faculty Of Economic And Business Of Islamic University Of Malang) - Sindi Wulandari; Abdul Kodir Djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT This study aims to know the Student Leadership Exercise (LKM) which is implemented by Students Association of Faculty of Economic of Islamic University of Malang (BEM-FE UNISMA) and also to know the improvement of work discipline in the organization after following the Student Leadership Training. The method use in this research is descriptive qualitative method. The result of this research is the achievement which is characterized by the competence of cognitive, affective and psychomotor. Where Leadership Training aims to provide understanding and quality improvement in the field of organization, leadership, conflict management, decision-making, anti-corruption and discipline education.Keywords        : LKM, Discipline Quality Improvement, Students Association   (BEM)